Epidemiology and clinical characteristics of Staphylococcus aureus bloodstream infections in a tertiary-care center in Mexico City: 2003-2007 - Camacho-Ortiz, Adrián; Macías, Alejandro E.; Landín-Larios, Carolina; Villanueva-Walbey, Constanza; Trinidad-Guerrero, Dayanira; López-Jácome, Esaú; Galindo Fraga, Arturo; Bobadilla-del-Valle, Miriam; Sifuentes-Osornio, José (My University, 2010)
To compare the epidemiology, clinical variables, outcome and molecular characteristics between methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) bloodstream infections (BSI) of patients from a tertiary-care center. We conducted a five-year retrospective cohort analysis of all patients with at least one peripherally-drawn blood culture positive for S. aureus. Patient characteristics, clinical data and outcome were analyzed, as well as microbiologic data. We included 444 isolates derived from 172 patients. The highest rate of MRSA BSI was observed in 2005 (4.9 cases per 1,000 patients). MRSA BSIs were more likely to be originated from a skin and soft tissue infection (OR 2.44, CI 95% 1.05-5.67, p = 0.03). The only significant risk factor for MRSA BSI was the mean length of hospital stay (OR 1.01; CI 95% 1.00-1.02, p = 0.002). A difference in inadequate initial treatment was noticed in MRSA BSI (OR 8.35 CI 95% 1.55-8.39, p = 0.002); but it had no impact on mortality. All MRSA isolates were SCCmec type II, and we did not find any resistance to vancomycin or linezolid. MRSA BSIs were associated with a prolonged hospital stay. We did not observe any difference in mortality between MRSA and MSSA BSIs. During the study period, we only identified SCCmec type II in MRSA isolates, which suggests that this infection was hospital- acquired.

Objetivo. Comparar la epidemiología, las variables clínicas, el desenlace y las características moleculares entre las infecciones del torrente sanguíneo (ITS) por Staphylococcus aureus resistente a meticiilina (SARM) y S. aureus sensible a meticilina (SASM) ocurridas en pacientes de un hospital de tercer nivel. Métodos. Es un estudio de cohorte retrospectivo que incluyó un análisis de los episodios de ITS ocurridos durante cinco años. Incluímos a todos los pacientes hospitalizados, mayores de 16 años y con al menos un hemocultivo positivo para S. aureus. Se incluyeron características de los pacientes, datos clínicos y desenlace. Se realizaron pruebas de susceptibilidad antimicrobiana y de tipificación molecular en todos los aislados clínicos.
Epidemiología y características clínicas de las infecciones por Staphylococcus aureus en el torrente sanguíneo en un centre de atención tercer nivel en la ciudad de México: 2003-2007